ESTIMATION OF THE URBAN HEAT ISLAND IN LOCAL CLIMATE CHANGE AND VULNERABILITY ASSESSMENT FOR AIR QUALITY IN DELHI - Babazadeh, Mina; Kumar, Parvendra (European Scientific Journal, ESJ, 2015)
Delhi experience the effect of high heat compared to the rural surroundings during hot seasons. This phenomenon is known as Urban Heat Island (UHI) which exerts a significant influence on local climate. Urban climate, land cover, land use, vegetation ratio and surface temperature have been cited as the main contributors to the UHI effect. This paper focuses on urban heat islands (UHI) as a specific problem expected to be exacerbated by local climate change. A simple formula has been used to calculate the urban heat island (UHI) from a set of land surface temperature data for observed temperatures by Landsat 7 and 8 and quantifies how this urban heat island effect on local climate change response strategy 2000- 2014. The aim is to identify climate sensitive urban patterns during summer, winter and monsoon months. The study reveals that the intensity of heat island varies from 3 CÂ° to 8 CÂ° and intensity is high during summer season compared to monsoon and winter seasons. In Delhi the formation of heat island is controlled by vegetation density. It has been found that UHI become bigger during cooling at night time. The urban heat island helps to decrease air quality during summer. UHI coupled with high land surface temperature conditions during summer season causes human discomfort and higher death rates in Delhi. These changes reflect sensitivity to variations in regional climate alone, so omit other factors such as changes in land use, emissions, land surface temperature, or synergies on size and shape of heat islands.